THE ILLOCUTIONARY AND PERLOCUTIONARY ACTS PRODUCED BY THE MAIN CHARACTERS OF “THE INTERNSHIP” MOVIE - Kevin Tedjasukmana; Josefa J. Mardijono (Institute of Research and Community Outreach - Petra Christian University, 2016)
This study is about the types of illocutionary and perlocutionary acts produced by the main characters of “The Internship” movie, especially in the interview scene when Billy and Nick as the main characters are having an online interview. The theory that the writer uses in this study is Searle & Vanderveken’s theory about speech act in order to analyze his data. This qualitative research revealed the writer’s method which he uses in doing the analysis of his data. The types of illocutionary act produced by Billy and Nick as the main characters are Assertive, Directive, Commissive, and Expressive. Furthermore, the study revealed that the perlocutionary act produced by the other main characters to decide Billy and Nick’s illocution is preferred and dispreferred social acts. To conclude, by reading this study, readers will be able to understand the use of speech acts by the main characters of “The internship” movie.